2016
DOI: 10.1063/1.4960704
|View full text |Cite
|
Sign up to set email alerts
|

Double-gated Si NW FET sensors: Low-frequency noise and photoelectric properties

Abstract: A pH sensor with a double-gate silicon nanowire field-effect transistor Appl. Phys. Lett. 102, 083701 (2013) The transport, noise, and photosensitivity properties of an array of silicon nanowire (NW) p þ -p-p þ field-effect transistors (FETs) are investigated. The peculiarities of photosensitivity and detectivity are analyzed over a wide spectrum range. The absorbance of p-Si NW shifts to the short wavelength region compared with bulk Si. The photocurrent and photosensitivity reach increased values in the UV r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The InAs segment is shorter than the Si segment, namely 200 -500 nm vs 3 -4 μm. Energy-Dispersive X-ray Spectroscopy (EDS) was used to determine the NW composition, revealing that the brighter regions in the SEM micrographs are indeed InAs, 6 while the darker contrast segment consists of Si, as expected from the different atomic number (see Fig.1).…”
Section: Experimental and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The InAs segment is shorter than the Si segment, namely 200 -500 nm vs 3 -4 μm. Energy-Dispersive X-ray Spectroscopy (EDS) was used to determine the NW composition, revealing that the brighter regions in the SEM micrographs are indeed InAs, 6 while the darker contrast segment consists of Si, as expected from the different atomic number (see Fig.1).…”
Section: Experimental and Samplesmentioning
confidence: 99%
“…Si NW near-infrared photodetectors 5 or double-gated Si NW FET sensors. 6 On the other hand, III-V semiconductors present higher values of the carrier mobility and improved optical properties with respect to their group IV counterparts, thus making up for Si drawbacks. The integration of Si/III-V heterostructures in a single NW would allow combining the advantages of both Si and III-V semiconductors with the unique optical properties of semiconductor NWs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows a fabricated micro uidic chip device with picolitre bioreactors (PLBR) for cultivation and investigation of bacteria on the single cell level Grünberger et al (2012). ( (Gasparyan et al, 2016) Figure 5 shows double gates Si NW FET arrays for biological signal detection. The transport, noise, and photosensitivity properties of an array of silicon nanowire (NW) p+-p-p+ eld-e ect transistors (FETs) shows an shift of absorbance of p-Si NW to the short wavelength region compared with bulk Si.…”
Section: Nanoelectronicsmentioning
confidence: 99%
“…Noise behavior is successfully explained in the framework of the correlated number-mobility uni ed uctuation model. pH sensitivity increases as a result of the increase in liquid gate voltage, thus giving the opportunity to measure very low proton concentrations in the electrolyte medium at certain values of the liquid gate voltage (Gasparyan et al, 2016).…”
Section: Nanoelectronicsmentioning
confidence: 99%
“…Note that the excess noise level at the DNA sequencing using the solid-state nanopores (which a few tens of pA to 100 pA, 10 times larger than that of protein counterparts [3] The numerical and analytical theory of signal and noise of double-gated pH-sensors was provided in [14]. The transport and noise properties of an array of silicon nanowire FET sensors are investigated in [15]. It is shown that drain current substantially depends on pH value and SNR reaches the high value of 10 5 .…”
Section: Introductionmentioning
confidence: 99%